WOMEN’S LANGUAGE FEATURES USED BY SARAH SECHAN IN HER TALK SHOW - Maria Catharina Gustia Apridaningrum; Patricia Angelina (ELTR Journal, 2019)
Every human being needs to communicate to each other. Men and women are different in terms of using a language or languages in their daily conversation. Women’s language proved that women tend to use language differently than men, it is shown in features they use. Sarah Sechan is one of well-known, multitalented, communicative, and creative presenters in Indonesia. It is proved by the words choices in her speech. So, the researcher chose her to be one of the instruments in gathering the data. Therefore, the researcher build a research question as follows : What are the women’s language features used by Sarah Sechan? The researcher used qualitative data methods by employing content analysis to answer the research question. There were 2 research instruments used in this research. They were the researcher as the human research and observation sheet. In this research, the researcher found that nine features were used, there were:. 48 empty adjectives (23.415%), 44 intensifiers (21.463%), 35 features of lexical hedges (17.073%). 18 features of tag question (8.780%), 16 hyper-correct grammar (7.804 %), 15 features of rising intonation (7.317%), 11 Super-polite (5.366%), 9avoidance of strong swear words (4.390%), and 9 features of emphatic stress (4.390%).